CTA Project Completion Report: Scaling up Climate-smart Agricultural Solutions for Cereal and Livestock Farmers in Southern Africa - Ajayi, Oluyede C.; Kadzamira, Mariam A.T.J.; Bailly, Alicia (Technical Centre for Agricultural and Rural Cooperation, 2020)
Working with a consortium of partners including the private sector (telecommunications, seed companies), government agencies (extension departments, climate change and meteorology departments), producer organisations (Zimbabwe Farmers Union, National Association of SmallScale Farmers NASFAM, Southern African Confederation of Agric Unions SACAU), knowledge centres on climate change (weather data companies, universities), the project’s aim was to deliver bundle of CSA solutions to smallholder farmers using ICT-enabled extension mechanism, innovative partnership and facilitated support environment. CTA’s activities in response to climate change has focused on helping to build the resilience of farmers to climate change by scaling an integrated bundle of climate solutions to farmers through a consortium of partners and models of partnership models.